The Implementation of Project-Based Learning Model with Instagram Media towards Students’ Critical Thiking and Creativity (Unnes Science Education Journal, 2022)
The 21st- century learning is oriented on 21st-century competencies, such as critical, creative, communicative, and collaborative thinking skills. These are important to be instilled and can develop the learners’ skills. One of them is to develop creativity and motivation for the learners. A project-based learning model with Instagram is a suggested learning model to allow learners to develop their skills. This research aims to analyze the Pjbl with Instagram as the media toward the learners’ creativity about invertebrate as the material. The applied method was Quasy Experimental research with Nonequivalent Control Group Design. The population consisted of the tenth graders of the Science and Mathematics class of Public Senior High School 1 Ungaran, in the academic year 2020/2021. The findings showed that the critical thinking skills obtained an average score of 88.7. The result was higher than the minimum mastery standard, ≥ 75. Then, a t-test was done. The results showed that the learner's creativity was 90.1% for the experimental group. Both of them obtained “excellent criterion”. Based on the results, it could be concluded that the Pjbl with Instagram as the media could improve the critical and creative thinking skills of the learners.